Refining IOPT Petri Nets Class for Embedded System Controller Modeling - Gomes, Luís (2019)
Since its inception, the Input-Output Place-Transition (IOPT) class of Petri nets have changed in response to the gained experience in the use of its associated tools freely available as a cloud based toolset. Here, we informally present the current state of the IOPT net class as supported by the IOPT-Tools, publicly available at http://gres.uninova.pt/IOPT-Tools/. The corresponding formal syntax and semantics are presented, followed by an illustrative example. Finally, we give a brief presentation of the respective XML-based interchange format and conclude.